Enhanced expectancies in golf putting - a replication study with increased ecological validity - Ziv, G.; Lidor, R.; Lavie, M. (International Journal of Sport and Exercise Psychology, 2021)
The performance of motor tasks can be improved by enhanced performance expectancies. The purpose of the current study was to examine whether providing relatively easy performance criteria to golfers improves their golf-putting accuracy. More specifically, our aim was not only to replicate a previous study (Ziv, G., Ochayon, M., & Lidor, R. 2019. Enhanced or diminished expectancies in golf putting - Which actually affects performance? Psychology of Sport and Exercise, 40, 82-86), but also to strengthen the ecological validity of the putting task in the study by adding an actual golf hole to the putting environment. Forty-five physical education students were randomly assigned to three learning groups: (a) a large-circle group, (b) a small-circle group, and (c) a control group (no circle). They all performed 50 putts from a distance of 2 m. We informed the participants in the large-circle and the small-circle groups that landing the golf ball inside the circle would be considered a successful trial. Two days later, the participants performed a retention test of 12 putts followed by a transfer test of 12 putts from 2.5 m. The participants who putted with the larger circle around the hole showed a lower absolute error than the control participants in the acquisition putts. In addition, these participants showed a lower absolute error and an increased number of holed putts compared to the participants in the control group in the transfer test. The results suggest that placing a relatively large circle around a golf hole in practice can lead to improved putting performance.